2018
DOI: 10.2147/opth.s165875
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of axial length measurements obtained by optical biometry and acoustic biometry in rhegmatogenous retinal detachment: a prospective study

Abstract: PurposeWe compared the accuracy of axial length (AL) measurement obtained by optical biometry with that obtained by acoustic biometry in eyes with rhegmatogenous retinal detachment (RRD).Patients and methodsThis prospective descriptive analytic study measured the AL of eyes with RRD preoperatively and 3 months postoperatively using optical biometry (intraocular lens [IOL] master group) and acoustic biometry (immersion A-scan group). Preoperative and postoperative measurements were compared by paired t-test. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…As the advances emerging in microsurgical instrumentation on small-gauge vitrectomy, combined surgery has, therefore, become a popular procedure in treating RRD [5][6][7] . A high level of consistency of AL measured before and after PPV has been shown in both macula-sparing RRD cases [8] and macula-off RRD cases [1,2] . In RRD cases treated by combined surgery, selection of the IOL power using AL data measured before PPV is reported to result in a small biometric error and a small myopic shift that is within the tolerable range in most cases [9] .…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…As the advances emerging in microsurgical instrumentation on small-gauge vitrectomy, combined surgery has, therefore, become a popular procedure in treating RRD [5][6][7] . A high level of consistency of AL measured before and after PPV has been shown in both macula-sparing RRD cases [8] and macula-off RRD cases [1,2] . In RRD cases treated by combined surgery, selection of the IOL power using AL data measured before PPV is reported to result in a small biometric error and a small myopic shift that is within the tolerable range in most cases [9] .…”
mentioning
confidence: 75%
“…It has been reported the macula-off status may in uence the measurement of AL [1,2] . We ruled out macular-on cases to lessen the impact of macular-on status on AL measurement.…”
Section: Factors That May Be Related To the Variation Of Al Measuredmentioning
confidence: 99%
See 1 more Smart Citation
“…Both ultrasound (US) A-scan biometry and non-contact PCI based devices are used for calculating IOL power 6,8 . AL in ultrasound method is measured from corneal vertex to the internal limiting membrane (ILM) 9 . The ultrasound biometry can be performed by applanation of the probe to the corneal surface or by indirectly contact of probe to corneal surface in immersion technique (by using saline filled shell).…”
Section: Introductionmentioning
confidence: 99%
“…Another advantage of non-contact Biometer over ultrasound contact method is to provide different IOL power formulas for single IOL model, however, it is unable to measure biometric parameters in dense cataract 12 . Therefore, in all cases ultrasound biometry cannot be replaced by non-contact biometry 9,13 . A recent study on comparison between contact and noncontact biometry reported that both techniques were comparable with no clinical significant difference in measuring AL 13 .…”
Section: Introductionmentioning
confidence: 99%